علاقات حضارية سلمية متبادلة بين المسلمين والصليبين خلال الحروب الصليبية 492 - 690 هــ - 1095 - 1291 م - الشريدة، خالد سليمان (الجامعة الأردنية - عمادة البحث العلمي, 2017)
This study investigates the foundations of civilizd communication between Muslims and Crusaders during the Crusades to the Levant and the contemporary Prince Osama bin Mongheth savior of these deceased war in 544 AH-1888 and then of the crusader Wiliam Suri, who died in 581 AH- 1185 AD and Fulcher of Chartres deceased in BC 12-6 e and traveler Ibn Jubayr, who died in 614 AH- 1218 AD, Ibn Shaddad, who died in 632 AH- 1234 AD who this war contemporary enrich and reflect more than others in this social aspect in terms of coexistence and understanding and communication between the various demographic elements that formed Shami community during the Crusades and inspired by the predominance recipe peace not war on this relationship, vulnerability and influence another between the Muslim and Crusader parties through a common language and means of addressing concerted by the friction between the parties and mating and affinity of each other sometimes and the impact of religion and belief of the parties in each other and we were the piece of material and moral heritage of mutual then we pointed to what some people taking it from each other from this positive heritage, habits and behaviors that have left their social impacts in the behavior of subsequent generations and we mentioned at the end of this research was reportedly referring some of the continued existence of a cruciform family after the departure of the Crusader forces from the region, through Shami families said to be related to the proportions since those invading Crusader campaigns in the Islamic eastern areas.
بحثنا واستقينا المعلومة في هذه الدراسة الاجتماعية الجادة في الجوانب الحضارية والعلاقات المتبادلة بين الطرفين: الإسلامي والصليبي، من مختلف المصادر الأصيلة والدراسات الثانوية، من خلال أسس التواصل الحضاري بين المسلمين والصليبيين خلال الحملات الصليبية على بلاد الشام، وكان للأمير المؤرخ أسامة بن منقذ المعاصر لهذه الحرب المتوفى سنة 584هـ/1188م، ثم المؤرخ الصليبي وليم الصوري المتوفى سنة 1185م/581هـ، وفوشيه الشارتري المتوفى في ق12م/6هـ، والرحالة ابن جبيرالمتوفى سنة 614هـ/1218م، وابن شداد المتوفى سنة 632هـ/1234م، ممن عاصر هذه الحرب إثراءٌ وتمعنٌ أكثر من غيرهم في هذا الجانب الاجتماعي، من حيث التعايش والتواصل والتفاهم بين مختلف العناصر السكانية التي شكلت المجتمع الشامي خلال الحروب الصليبية، وأوحت بغلبة صفة السلم لا الحرب على هذه العلاقة، والتأثر والتأثير بالآخر بين الطرفين المسلم والصليبي من خلال لغة مشتركة، ووسائل تخاطب متفاهم عليها بالاحتكاك، وتزاوج ومصاهرة بين هذه الأطراف أحياناً، وأثر ديانة ومعتقد الطرفين في بعضهما البعض.
Keywords: التاريخ الإسلامي -- الحضارة الإسلامية -- الحروب الصليبية -- الإسلام -- المسلمين -- المصادر التاريخية